Pengembangan Media Video Animasi Berbantuan Capcut pada Pembelajaran IPS Materi Indahnya Keragaman di Negeriku Kelas IV Sekolah Dasar - Priskalia Putri; Muhamad Idris; David Budi Irawan (Innovative: Journal Of Social Science Research, 2023)
The development of animated video as media intends to assess the viability of students responses to the animated video in "Indahnya Keragaman Dinegriku" on social studies class IV in elementary school. This research study was carried out at SD Negri 229 in Palembang. 24 students from class IV C served as the study's research subject. Furthermore, Sivasialam Thiagarajan's 4D (four dimension) approach, which comprises of four steps, including Define, Design, Develop, and Disseminate was applied in this study as the research method. Experts in media approved this animated video, and then tested the product to the students. As a result, this research come out with the validity test's rate of 86.15%, and it is classified as very valid as well as very practical rating of 86.54 was assigned to the product test rate. Therefore, it can be concluded that the use of animated film in "Indahnya Keragaman Dinegeriku" on social class is highly acceptable.